Purumllaqta de Cuimal and the area of San Jerónimo (Amazonas) during the Inca hegemony - Villar Quintana, Anthony (2020)
This article addresses the issue of Inca hegemony in the area of the current community of San Jerónimo, on the left bank of the Utcubamba River, Amazonas. Considering mainly the site of Purumllaqta de Cuimal and its relationship with the funerary structures of Cerro El Tigre and the rock art sites of Suinte, Ayasamana and Chumoc, we approach the importance of this area for the Tahuantinsuyo.